PENGARUH OCCUPATIONAL STRESS DAN PSYCHOLOGICAL CONTRACT TERHADAP WORK ENGAGEMENT MELALUI PSYCHOLOGICAL WELL BEING DI SAAT PANDEMI COVID 19 (Studi pada Karyawan KCP Bank Jateng Pasar Johar) - Herlina Damayanti; Ali Mursid (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
Psychological well-being as a prerequisite for work engagement through the expression of physical, cognitive and emotional resources. This, refers to the state of happiness in work assignments. The purpose of this study was to analyze the effect of occupational stress and psychological contract on work engagement through psychological well being as an intervening variable. The sample of this study was 33 people from a population of 33 employees KCP Bank Jateng Pasar Johar. The method of determining the sample using saturated sampling. Data analysis using multiple linear regression models with two models and multiple tests. The results of testing the first model hypothesis shows that occupational stress has a statistically significant and negative effect on psychological well being and psychological contract has a statistically positive and significant effect on psychological well being. The results of testing the second model hypothesis show that psychological well being statistically has a positive and significant effect on work engagement, occupational stress has a statistically negative and significant effect on work engagement and psychological contract has a positive and significant effect on work engagement. Hypothesis testing results show that occupational stress is calculated independently that there is an indirect effect on work engagement, namely through psychological well being as an intervening variable and psychological contract by means of calculation that there is an indirect effect on work engagement, namely through psychological well being as an intervening variable